Immobilisation of xylanase for xylooligosaccharides production from meranti wood sawdust - Siti Sabrina, Mohd Sukri (2018)
The limitations of free or soluble enzyme such as non-reusability, poor stability, and sensitivity to denaturation could be handled by the use of immobilised enzymes. Generating a value-added product, xylooligosaccharides (XOS) from new renewable material, Meranti wood sawdust (MWS) by the used of immobilised xylanase are currently an object of interest due to their benefits over soluble xylanase. The aim of this study is to immobilise xylanase for XOS production from MWS by enzymatic hydrolysis. Xylan from MWS was extracted using a standard chlorite holocellulose method. Prior to enzymatic hydrolysis, immobilised xylanase was prepared using a different technique of immobilisation comprised of a single entrapment, single covalent binding, and a combination of entrapment and covalent binding. The immobilisation conditions were optimised using a systematic experimental design which includes one-factor-at-a-time (OFAT) to study the effects of each parameter, followed by fractional factorial design (FFD) used for screening process to determine the significant parameters, and finally, optimisation by response surface methodology (RSM) to obtain maximum xylanase immobilisation yield. The results showed that xylan content in MWS was 21.89% and the recovery yield of xylan after extraction was 39.45% of original xylan available in MWS. For the immobilisation of xylanase, a combination technique of entrapment and covalent binding showed the highest immobilisation yield (65.83%) compared to single techniques which yielded only 31.98% and 48.46%, respectively. The optimum xylanase immobilisation conditions by RSM were obtained at 16.76% (w/w) of glutaraldehyde concentration, 3.13% (w/v) of sodium alginate concentration, and 178 U of enzyme loading with a maximum immobilisation yield of 82.61%. Immobilisation improved the pH stability from 7.0 to 8.0 and thermal stability by shifting the optimum temperature from 50 to 60 °C. Thermodynamic study indicated that immobilised xylanase slightly lowered the Ea from 15.24 to 14.80 kJ∙mol−1, which improves the catalytic efficiency of xylanase. The immobilised xylanase also exhibited a good operational stability, retaining about 81% and 60% of its initial activity during the second and third process cycles. The optimised immobilised xylanase then was applied in enzymatic hydrolysis to degrade the MWS xylan and the production of total XOS and its derivatives were compared to the reaction of free xylanase with commercial xylan. The highest total XOS yield obtained from MWS xylan by the reaction of immobilised xylanase was 53.61 mg/g at their best hydrolysis conditions at 2% (w/v) of substrate concentration, 48 h of hydrolysis, and 55 °C. During hydrolysis, the immobilised xylanase released a lower degree of polymerisation (DP) of XOS, mainly xylobiose (X2), xylotriose (X3), and xylotetraose (X4) from the degradation of MWS xylan, which are the preferable types of oligomers, particularly for food industry applications. From the reusability study, immobilised xylanase in the XOS production was able to retain 70% of its initial XOS production during the second cycle with five consecutive cycles. With respect to economic feasibility and industrial application, the MWS demonstrated the potential as a new source of xylan substrate for XOS production. Immobilised xylanase by a combination technique also showed good results in terms of stability and recycling efficiency for continuous hydrolysis.